Training Needs Analysis for Induction Training of State forest Service Officers - Singh, M. P.; Jayachandran, K. S. (Indian Forester, 2018)
The paper makes a review of the training needs of Assistant Conservators of Forests, aiming at scientific design of relevant and modern curriculum for induction training course of State Forest Service (SFS) officers. During the last few years, there is voluminous data generated at the Directorate of Forest Education which is being evaluated during the present review through a set of focused group discussions. The analysis concludes that present advances in science and technology and availability of superior management tools and techniques, has necessitated reorientation and revamping of induction training of Assistant Conservators of Forests to instill a holistic understanding of forestry and natural ecosystems.